2016
DOI: 10.1159/000446185
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Biometric Parameters Predict the Vault after ICL Implantation: A Retrospective Clinical Study

Abstract: Purpose: To investigate the correlation between the preoperative biometric parameters of the anterior segment and the vault after implantable Collamer lens (ICL) implantation via this retrospective study. Design: Retrospective clinical study. Methods: A total of 78 eyes from 41 patients who underwent ICL implantation surgery were included in this study. Preoperative biometric parameters, including white-to-white (WTW) diameter, central corneal thickness, keratometer, pupil diameter, anterior chamber depth, sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…Our multiple regression analysis yielded a result close to the highest linear fitting value reported in previous vault prediction studies (adjusted R 2 = 0.411) [6][7][8][9][10]. However, linear regression analysis explained no more than half of the vault prediction.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our multiple regression analysis yielded a result close to the highest linear fitting value reported in previous vault prediction studies (adjusted R 2 = 0.411) [6][7][8][9][10]. However, linear regression analysis explained no more than half of the vault prediction.…”
Section: Discussionsupporting
confidence: 84%
“…ICL implantation remains challenging because of difficulties in determining the appropriate lens size and predicting the vault value. Recent studies utilizing regression analyses have reported that the postoperative vault can only be explained in approximately 41.0% of cases [6][7][8][9][10]. In the present study, we performed linear regression and neural network analyses to examine the relationship between the preoperative biometric variables and the postoperative vault.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The need for predicting the vault has led to the development of predictive models using biometric and lens features. 7 – 11 Despite the variety of associations put forward, the ability of explaining the vault preoperatively is limited to approximately 40% 9 , 10 and decreases to 14% if the prediction is restricted to an optimal vault range. 12 Several arguments have been presented to justify the limited predictability of the models.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we speculated that pupil constriction due to the disappearance of the effect of the mydriatic agent played a very important role in vault reduction within 1 day after surgery. Finally, several studies have proven that the morphology of the crystalline lens also has an in uence on vault after ICL implantation [32][33][34]. ICL vault was affected by changes in crystalline lens rise (CLR) caused by accommodation or light condition changes [20,35,36].…”
Section: Discussionmentioning
confidence: 99%